2019
DOI: 10.1038/s41539-019-0059-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity links performance in science reasoning with conceptual approach

Abstract: Understanding how students learn is crucial for helping them succeed. We examined brain function in 107 undergraduate students during a task known to be challenging for many students—physics problem solving—to characterize the underlying neural mechanisms and determine how these support comprehension and proficiency. Further, we applied module analysis to response distributions, defining groups of students who answered by using similar physics conceptions, and probed for brain differences linked with different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
12
0
3
Order By: Relevance
“…Instruction regarding conceptual understanding of scientific concepts should aim to disclose students' prior knowledge and assumptions about the concept of interest. Additionally, explicit attention to metacognitive components of learning may also facilitate the putative control processes that are involved in concept learning (Allaire-Duquette et al, 2019;Bartley et al, 2019).…”
Section: Implications For Science Educationmentioning
confidence: 99%
“…Instruction regarding conceptual understanding of scientific concepts should aim to disclose students' prior knowledge and assumptions about the concept of interest. Additionally, explicit attention to metacognitive components of learning may also facilitate the putative control processes that are involved in concept learning (Allaire-Duquette et al, 2019;Bartley et al, 2019).…”
Section: Implications For Science Educationmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) is a particularly powerful tool for evaluating changes in the spatial distribution of neural activity in response to instruction. Characterization of the neural networks involved in scientific reasoning is a relatively new endeavor, although studies from the last 25 years have established the ability of fMRI to provide insight into the neural bases of scientific reasoning and the effects of different instructional formats on these neural mechanisms (e.g., Masson et al, 2014;Kontra et al, 2015;Mason and Just, 2015;Bartley et al, 2019;Schwettmann et al, 2019). For example, Kontra et al (2015) used fMRI to examine the impact of different instructional methods in physics.…”
Section: Learning Transfer From System-specific Contexts To System-gementioning
confidence: 99%
“…Because these areas have been linked to working memory and higher-level reasoning, the authors suggested that MBI might support students' use of mental simulation and prediction generation. Moreover, students used different neural networks during sequential phases of reasoning, drawing initially on brain regions associated with higher-level working memory and proceeding to regions linked to visual information processing and memory retrieval (Bartley et al, 2019). Notably, this study involved pre-and postsemester MRI scans, as opposed to evaluating the effects of MBI relative to other forms of instruction.…”
Section: Learning Transfer From System-specific Contexts To System-gementioning
confidence: 99%
See 2 more Smart Citations